Evaluating the value of p70s6k and mTOR signaling pathway in monitoring exercise-induced central fatigue in rats: The p70s6k and mTOR in monitoring exercise-induced central fatigue - He, Guojian; Jiang, Hongsheng; Zhang, Enru; Wan, PengFei; Liu, GuangHui; Ji, Zhimin (Cellular and Molecular Biology, 2022)
Exercise leads to muscle fatigue and decreased muscle strength in response to contraction activity, and besides, it causes central fatigue. In the current study, we evaluated the value of p70s6k and mTOR signaling pathways in monitoring exercise-induced central fatigue in rats. For this purpose, 12 male rats were divided into control (n=6) and intervention (n=6) groups. The intervention group performed five sessions of climbing a one-meter ladder with a weight hanging on the tail for eight weeks. The weekly load increase was based on the mice's body weight, so it reached 30% in the first week to 200% in the eighth week. In order to evaluate central fatigue, the sedation score system was used. Forty-eight hours after the last training session, a blood sample was prepared, the expression level of related proteins was measured by the ELISA method, and the one-way ANOVA method was used for statistical analysis. This study showed that central fatigue did not significantly affect the total mTOR protein content (F=0.720, P=0.421). However, the level of phosphorylated mTOR in the intervention group had a significant difference compared to the control group (F=684.893, P=0.001, Eta2=0.988). There was a significant effect for total p70S6K content (F=5.84, P=0.04, Eta2=0.42). Also, for phosphorylated p70S6K, there was a significant difference between the mentioned groups (F=7.262, P=0.027, Eta2=0.476). In General, it was shown in this study that central fatigue is directly related to the increase in p70S6K production and phosphorylation of p70S6K and mTOR. Therefore, these two proteins can probably be evaluated for monitoring exercise-induced central fatigue, although we need more evaluations.